Employability resources of unemployed adults: longitudinal effects of a group career intervention - Catarina Luzia de Carvalho; João Marôco; Maria do Céu Taveira; Ana Daniela Silva (Frontiers in Psychology)
IntroductionThis study evaluates the efficacy of a group-based career intervention designed to promote employability resources among unemployed individuals conducted in face-to-face and online modalities.MethodsEmploying a longitudinal quasi-experimental design, with two intervention groups and a control group, data was collected pre-, post, and two months post-intervention.ResultsConditional Latent Growth Curve analysis revealed a significant decline in employability resources over time, mitigated by both intervention groups. Human capital and professional development were key at baseline and follow-up, while social capital and networking were crucial post-intervention. Career identity self-career management, and environmental monitoring resources significantly contributed to employability post-intervention.DiscussionThese findings highlight the intervention’s effectiveness in counteracting the negative trend among the general population, underscoring the critical role of ongoing participation in career development activities for unemployed individuals. More empirical research on this type of initiative is encouraged, along with civil society taking responsibility for addressing the psychological challenges of unemployment.